Does Gender Differences Exist in Online Newspaper Consumption among Pakistani Youth? - Pahore, Muhammad Ramzan; Memon, Sumera; Hamid, Norsiah Abdul; Ismail, Awan Bt (Jurnal The Messenger, 2021)
It is no doubt that the popularity of ICTs in developing countries has increased the use of internet-related social networking sites along with news information consumption, production, and news distribution. As such, there has been a huge shift in the trend of news consumption from conventional media to an online newspaper. It has also been tocied that male and female youth are equally inclined to use internet for different reasons. Thus, in recent times scholars have started inspecting online newspaper consumption-related behavior, with an emphasis on young boys and girls in a way this group is one that can last longer. However, very few studies have paid attention to gender differences in motivating factors for online newspaper consumption in Pakistan. To address this gap, by using a cross-sectional design, a survey was conducted on university students from three public universities of Pakistan because university students are tech-savvy and mostly internet users. These three universities are representative of rural and urban population. Questionnaires were used to collect data which was analyzed using Partial Least Squares-Multi Group Analysis. Hypothesized results discovered that in terms of online newspaper consumption, there was no gender differences found in online newspaper consumption among Pakistani youth.